New combination for a species of the genus Serjania (Sapindaceae -Paullinieae) endemic in Mexico - Ferrucci, María S.; Medina-Lemos, Rosalinda (Instituto de Ecología, A.C., 2013)
The new combination Serjania pygmaea (Radlk.) Ferrucci & Medina (Sapindaceae-Paullinieae), based on Cardiospermum pygmaeum Radlk., is here provided. Cardiospermum pygmaeum was known only from the type, a flowering collection from Puebla, Mexico. We present a full description and an illustration of the species. Finally, Serjania pygmaea is compared to the morphologically similar Mexican species of Serjania.